Green Synthesis and Formation of Silica Nanoparticles Based on Natural Spondias mombin Leaf Extract for Renewable Energy Materials - Yoki Yulizar; Sri Mulijani; Armi Wulanawati (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2026)
Silica is an abundantly available material, with applications including renewable energy materials (fuel cells). Silica has been produced using natural materials (green synthesis) to form smaller and more stable particles, primarily due to the influence of secondary metabolites such as those contained in the leaf of Spondias mombin, a species of flowering plants from Lannea coromandelica (Houtt.) Merr and the family Anacardiaceae. The characteristics of silica nanoparticles obtained by green synthesis using the Spondias mombin leaf in a water fraction at 0,6 % were identified using XRD, FTIR, PSA, TGA, SEM, and TEM. Based on the XRD pattern and SEM/TEM images, the nanoparticle is amorphous and has a particle size of 20-30 nm, smaller than that of its precursor, which is 37.6 nm. There are Si-OH and Si-O-Si groups in the FTIR spectrum as an indication of the interaction between silica nanoparticles and secondary metabolites, and the zeta potential based on PSA is -45.9 mV. This indicates that silica nanoparticles have good stability and are supported by high thermal stability based on the results of the TGA analysis. This is correlated with its use as a material composite in renewable energy (fuel cells).